A framework for physical asset risk management in the Sri Lankan clothing industry. (13th November 2020) - Premanathan, Thatshayini; Rajini, Damitha; Karunaratne, Tharindu Lakruwan Wickremanayake
Increasing demand for operational efficiency in clothing manufacturing organisations necessitates the management of risks associated with their physical assets. The aims to develop a framework for effective physical asset risk management (PARM) in Sri Lankan clothing industry. This was approached through a multiple case study research method carrying out five case studies. The required data were collected through semi-structured interviews and the data analysis was carried out using content analysis. The research findings revealed that PARM in Sri Lankan clothing industry has not received an adequate attention. Adopting standardised risk management (RM) procedures, convincing the top management about the importance of PARM and achieving top management support and making the stakeholders aware about PARM are the keys to achieve effective PARM in Sri Lankan clothing industry. The PARM framework will be a useful guide for the practitioners in the clothing industry to manage physical asset related risks effectively.